Immunohistochemical WWOX Expression and Association with Angiogenesis, p53 Expression, Cell Proliferation and Clinicopathological Parameters in Cervical Cancer - Mariana Ataydes Leite Seabra; Eduardo Batista Cândido; Paula Vieira Teixeira Vidigal; Rivia Mara Lamaita; Angélica Nogueira Rodrigues; Agnaldo Lopes da Silva Filho (Revista Brasileira de Ginecologia e Obstetrícia, 2018)
Abstract Objective The current study evaluated the expression of WW domain-containing oxidoreductase (WWOX), its association with clinicopathological features and with p53, Ki-67 (cell proliferation) and CD31 (angiogenesis) expression in patients with invasive cervical squamous cell carcinoma (ICSCC). To the best of our knowledge, no other study has evaluated this association. Methods Women with IB stage-ICSCC (n = 20) and women with uterine leiomyoma (n = 20) were prospectively evaluated. Patients with ICSCC were submitted to type BC1 radical hysterectomy and pelvic lymphadenectomy. Patients in the control group underwent vaginal hysterectomy. Tissue samples were stained with hematoxylin and eosin for histological evaluation and protein expression was detected by immunohistochemistry studies. Results The WWOX expression was significantly lower in the tumor compared with the expression in thebenign cervix (p = 0.019). TheWWOXexpressionwas inversely associated with the CD31 expression in the tumor samples (p = 0.018). There was no association betweentheWWOXexpression with the p53 expression (p = 0.464)or the Ki-67expression (p = 0.360) in the samples of invasive carcinoma of the cervix. There was no association between the WWOX expression and tumor size (p = 0.156), grade of differentiation (p = 0.914), presence of lymphatic vascular invasion (p = 0.155), parametrium involvement (p = 0.421) or pelvic lymph node metastasis (p = 0.310) in ICSCC tissue samples. Conclusion The results suggested that WWOX may be involved in ICSCC carcinogenesis, and this marker was associated with tumor angiogenesis.